If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(p-8)=12
We move all terms to the left:
3(p-8)-(12)=0
We multiply parentheses
3p-24-12=0
We add all the numbers together, and all the variables
3p-36=0
We move all terms containing p to the left, all other terms to the right
3p=36
p=36/3
p=12
| 40/y=8 | | 11p-31=4p+25 | | 2(6r-7)=70 | | 3(6m+3)=63 | | 8x+28=13x+13 | | x^2+16=78 | | 8(2a-3)=60 | | 5(x+3)=5x-4 | | 12-8r=-60 | | 4(3a-5)=7(6-2a) | | 5l+4=2l-8 | | 24=6/t | | -3b=148 | | 7(c+6)=105 | | 9=(5y-3) | | 6+9=c | | -2j=-34 | | (4x)^(-2)(4x)^(3)(4x)^(9)=(4x) | | 72=8(x+9) | | 11w–4=7= | | 2x+10=-44x-7x | | 7y–3=18= | | 6x-3x+4x+x=7x | | –y–1=-2y | | 36/24=x/16 | | 4(3x-5)=30 | | 2x+6=123 | | 10x-9=8x+10 | | 10x-9=8+10 | | 7x=12-13x1-4x13 | | 3+5x=-12+x | | 14=5n=4 |